Owner's Responsibilities of Vehicles Used as Illegal Public Transport When Traffic Accidents Happened - Hesti Kristi Wahyudi; Sri Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
The research objectives to be taken in the intended research plan are as follows: To know and analyzecriminal law construction for owners of vehicles used as public transportation or commercialized. To find out and analyzeconstruction of criminal law is the responsibility of owners of vehicles commercialized as public transportation. To find out and analyzesolution to the problem of responsibility of vehicle owners who commercialize their vehicles illegally when a traffic accident occurs on the highway. The method used by researchers isjuridical sociological approach to law and the specification in this research is including analytical descriptive. Based on the results of that research Construction based on criminal law Act No. 22 of 2009 concerningTraffic and road transportArticle 308 is a sanction for every person driving a public motorized vehicle not equipped with a license to carry out person transportation/not having a route. The construction of liability criminal law is based on Act No. 22 of 2009 concerningTraffic and road transport Article 315 states that when a criminal offense is committed by a Public Transportation Company, the criminal liability is imposed on the Public Transportation Company by adding a maximum fine of 3 (three) times the fines specified in each article and also subject to additional penalties in the form of temporary suspension or revocation transport operating license for the vehicle used.The obstacles: there are no articles in the Road Traffic and Transportation Act No. 22 of 2009 that can be used to ensnare vehicle owners. The solution is to hope that this article will exist so that in the future it can create a deterrent effect for vehicle owners so that they do not go around operating their vehicle without being equipped with existing terms and conditions in accordance with the law and in the future it is also expected to prevent the occurrence of traffic accident victims in large numbers.